Trends on paleoart in the paleontology research and public education: a thematic review - Lu, Zheng; Che Me, Rosalam; Rahmat, Rahmita Wirza O.K. (Malque Publishing, 2025)
Paleoart, the artistic representation of prehistoric life based on scientific evidence, plays a crucial role in paleontological research and public education. It serves as a bridge between scientific discoveries and public understanding, making complex paleontological data accessible and engaging. Despite its importance, there has been limited comprehensive analysis of the trends and historical development of paleoart within academic research and educational contexts. This gap hinders a holistic understanding of how paleoart has contributed to and been influenced by advancements in paleontological research and public education.Utilizing a thematic review (TR) methodology, this study incorporates keywords such as paleoart, paleontology, and education from the SCOPUS, WoS and Mendeley databases, and a total of 30 papers published between 2013 and 2024 were reviewed. The thematic analysis reveals three key themes: scientific and aesthetic decision, Integration of digital technology, and outreach impact. The findings highlight how paleoartists balance scientific fidelity with creative interpretation, addressing the challenges of reconstructing extinct organisms from incomplete fossil records. The integration of advanced digital tools, such as 3D modeling, augmented reality (AR), and virtual reality (VR), has significantly enhanced the accuracy, accessibility, and educational value of paleoart. This review underscores the need for continued exploration of technological innovations and interdisciplinary collaborations to further strengthen paleoart's scientific precision and artistic appeal. The findings also pave the way for future research into the specific impacts of paleoart on public understanding and educational outcomes. By informing strategies to optimize the use of paleoart in scientific communication, this research provides valuable insights for educators, researchers, and policymakers. Future studies should prioritize the development of standardized frameworks and guidelines for paleoart creation, ensuring its sustained evolution as a compelling medium for paleontological visualization and education.